2021
DOI: 10.3390/jof7070556
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Systemic Mycoses in the COVID-19 Pandemic

Abstract: The physiopathologic characteristics of COVID-19 (high levels of inflammatory cytokines and T-cell reduction) promote fungal colonization and infection, which can go unnoticed because the symptoms in both diseases are very similar. The objective of this work was to study the current epidemiology of systemic mycosis in COVID-19 times. A literature search on the subject (January 2020–February 2021) was performed in PubMed, Embase, Cochrane Library, and LILACS without language restrictions. Demographic data, etio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 114 publications
(494 reference statements)
0
28
0
2
Order By: Relevance
“…Moreover, Aspergillus spp., causes a life-threatening disease-invasive pulmonary aspergillosis (IPA) that is characteristically associated with immune-system dysregulation and affects the respiratory system. IPA chiefly arises due to the prolonged usage of glucocorticoids, immunosuppressive agents, chronic neutropenia, and in transplant recipients [124,125]. Case reports and observational studies have shown that COVID-19-associated pulmonary aspergillosis (CAPA) is of significant concern in hospitalized COVID-19 patients with complications [125,126].…”
Section: Candida and Other Fungal Infections In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Aspergillus spp., causes a life-threatening disease-invasive pulmonary aspergillosis (IPA) that is characteristically associated with immune-system dysregulation and affects the respiratory system. IPA chiefly arises due to the prolonged usage of glucocorticoids, immunosuppressive agents, chronic neutropenia, and in transplant recipients [124,125]. Case reports and observational studies have shown that COVID-19-associated pulmonary aspergillosis (CAPA) is of significant concern in hospitalized COVID-19 patients with complications [125,126].…”
Section: Candida and Other Fungal Infections In Covid-19mentioning
confidence: 99%
“…Case reports show that patients treated with steroids during COVID-19 treatment often developed histoplasmosis caused by a dimorphic fungus Histoplasma capsulatum [127]. Fungus histoplasmosis is highly endemic and has been found in regions of the United States (California), Rio Grande, Southern Brazil, Buenos Aires, and Argentina [124]. This fungus is found in soil containing the excreta of birds or bats [127] and is associated with immunosuppressive conditions [127,128].…”
Section: Candida and Other Fungal Infections In Covid-19mentioning
confidence: 99%
“…While the exact role of COVID in potentially increasing Coccidioides infections or reactivation remains incompletely defined, cases of co-infection have been reported in the literature. A review of systemic mycoses in the setting of SARS-CoV-2 infection reported two coccidioidal cases in California, one treated with fluconazole and the other without; there were no reported fatalities [ 159 ]. An additional case of accelerated progression of disseminated coccidioidomycosis following SARS-CoV-2 has been published [ 160 ].…”
Section: Novel Co-infectionsmentioning
confidence: 99%
“…In the High Specialty Regional Hospital of Ixtapaluca, according to the protocol for the care of pregnant women with COVID-19—which is based on the protocol for patients with hospital-acquired and ventilator-associated pneumonia—and before giving treatment with antibiotics, a battery of cultures is carried out at hospital admission (cervicovaginal, blood culture, urine culture, and stool culture). This is since in many of the COVID-19 cases at the beginning of the pandemic, Azithromycin and Doxycycline were used indiscriminately, which in addition to not having given positive results for the intubation and/or death of the patients, it had caused the generation of cross-resistance, as well as superinfection by resistant microorganisms (fungi, bacteria, and parasites) responsible for other infections associated with this pathology [ 53 , 54 , 55 ]. It should be emphasized that none of the patients attended at the hospital were treated with antibiotics before their admission.…”
Section: Findings In the Hraei Culturesmentioning
confidence: 99%